Effects of acetylcholine on neuronal properties in entorhinal cortex - Heys, James G.; Schultheiss, Nathan W.; Shay, Christopher F.; Tsuno, Yusuke; Hasselmo, Michael E. (Frontiers in Behavioral Neuroscience, 2012)
The entorhinal cortex receives prominent cholinergic innervation from the medial septum and the vertical limb of the diagonal band of Broca (MSDB). To understand how cholinergic neurotransmission can modulate behavior, research has been directed towards identification of the specific cellular mechanisms in entorhinal cortex that can be modulated through cholinergic activity. This review focuses on intrinsic cellular properties of neurons in entorhinal cortex that may underlie functions such as working memory, spatial processing and episodic memory. In particular, the study of stellate cells in medial entorhinal has resulted in discovery of correlations between physiological properties of these neurons and properties of the unique spatial representation that is demonstrated through unit recordings of neurons in medial entorhinal cortex from awake-behaving animals. A separate line of investigation has demonstrated persistent firing behavior among neurons in entorhinal cortex that is enhanced by cholinergic activity and could underlie working memory. There is also evidence that acetylcholine plays a role in modulation of synaptic transmission that could also enhance mnemonic function in entorhinal cortex. Finally, the local circuits of entorhinal cortex demonstrate a variety of interneuron physiology, which is also subject to cholinergic modulation. Together these effects alter the dynamics of entorhinal cortex to underlie the functional role of acetylcholine in memory.